Efektivitas Pemeriksaan Anak Korban Kekerasan Seksual Dalam Persidangan - Siti Nur’ain Habu; Mohamad Rusdiyanto U Puluhulawa; Jufryanto Puluhulawa (Pusat Riset dan Inovasi Nasional, 2024)
The examination of child victims of sexual violence in trials has not been effectively carried out in accordance with Law Number 11 of the Year, in trials of child victims of sexual violence the child victims must provide information again during the trial which has previously been explained during the inquiry and investigation process so that the child must remember again. incidents that make children afraid and traumatized, plus they have to meet the defendant or perpetrator who is someone who has caused trauma and damaged the child physically and psychologically, not to mention children who do not receive assistance and health and safety measures during the judicial process as in case number 117.Pid.Sus/PN LBo where the two child victims did not receive assistance from child protection agencies and from psychology for child safety and health efforts in accordance with Law Number 11 of the Year. This research uses an empirical juridical research method which is research and implementation in accordance with written legal provisions. Based on the results of the analysis of Law Number 11 of 2012, it provides protection and assistance to child victims, especially child victims of sexual violence, victims receive assistance treatment during the investigation and case investigation process until the completion of the case trial, but in fact in case 117.Pid.Sus/2022/ PN LBo, child victims experience deep trauma and even damage to the child's psychology, but there is no assistance from institutions that are experts in handling this case, such as women and children empowerment institutions, so that the examination of child victims of sexual violence in court has been effective but has not been carried out optimally.